370 Determination of macronutrient composition and amino acid digestibility of plant-based proteins for use in canine and feline diets. (7th December 2018) - Reilly, L; von Schaumburg, P; Hoke, J; Davenport, G; Utterback, P; Parsons, C; de Godoy, M
Abstract: Plant-based proteins are under-utilized as alternative protein sources in the pet food industry. Novel plant protein sources may alleviate symptoms associated with food sensitivities, and satisfy the growing consumer demand for vegan and vegetarian pet foods. However, there is little information regarding the chemical composition and suitability of these ingredients for pet nutrition. The objective of this study was to determine the macronutrient composition, standardized amino acid and nutrient digestibility of 14 novel, plant-based, protein ingredients. A variety of pulses (lentils, garbanzo beans), legumes (yellow peas, navy beans, black beans), and protein concentrates (pea, potato, faba bean, soy) were analyzed for dry matter, ash and organic matter (AOAC, 2006), crude protein (AOAC, 2006), gross energy (bomb calorimetry), acid hydrolyzed fat (AACC, 1983; Budde, 1952), and total dietary fiber (Prosky et al., 1992). Precision-fed rooster assays were conducted using cecectomized, Single Comb White Leghorn roosters (n=4/trt). The roosters were precision-fed 30g of a 1:1 ratio of an ingredient and corn mixture. Excreta were collected after 48h, freeze-dried, and analyzed for dry matter, organic matter, gross energy, and total nitrogen. Complete amino acid profiles (AOAC, 2007) were determined. For the protein concentrate sources, there were no significant differences in the digestibility of essential or non-essential amino acids, except methionine, which was lower ( P < 0.05) in faba bean protein concentrate. The legumes follow similar trends for essential amino acids, but have significant differences ( P < 0.05) in the digestibility of cysteine and tyrosine. All amino acids, with the exception of methionine in the legume sources, met or exceeded the minimal requirement set by the NRC (2006) for dogs and cats. It can be concluded that plant-based protein sources have the potential to become viable, novel, protein sources in canine and feline diets.